Can General Practitioners change outcomes in patients with acute coronary syndromes? Data from national registry PL-ACS - Poloński, Lech; Osuch, Marcin (Przewodnik Lekarza/Guide for GPs, 2007)
Acute Coronary Syndromes (ACS) are a major healthcare problem and represent a large number of hospitalizations. Diagnosis of ACS involves clinical assessment, laboratory tests and specific cardiac investigations. In patients with established diagnosis of ACS the management strategy should be selected on the basis of the perceived risk of serious complications. Conventional risk-factors have an influence on adverse prognosis after ACS. Thus, in addition to pharmacological therapy (double antiplatelet therapy, ACE-I, beta-blockers and statins must be administrated), life-style modification should be implemented in all cases. General practitioners play a major role in appropriate pharmacological treatment and secondary prevention after ACS.